Prinos ranom kršćanstvu i urbanizmu Tarsatike [A Contribution to the knowledge of Urbanism in Tarsatica and the Early Christian period of the Settlement] - NOVAK, Nino (Histria archaeologica, časopis Arheološkog muzeja Istre, 2007)
Ancient Tarsatica was founded as civitas peregrinorum during the second half of the 1st century along the right bank of the Rječina River right on its mouth in the Bay of Kvarner, on the site of a prehistoric harbour of Veli. Late Roman military headquarters within the system known as Claustra Alpium Iuliarum or Fortress Wall of the Iulian Alps located in the historic core of the city of Rijeka were an especially significant military point since the middle of the 3rd century. Clues exist that the transformation of urban into military settlement took place as soon as the end of the 2nd century. An Early Christian religious complex existing in the city in the 5th century was located at today’s Pul vele crekve Square. The Church of the Assumption of the Blessed Virgin Mary was built on the ruins of that three-naved basilica with a roofed narthex and annexes of memorial character. The floors of the basilica (dating from the 5th century) were covered in mosaics with geometric motifs, and the building itself indicates continuation of building tradition towards the Middle Ages, as well as an early reception of Christian religion in the Kvarner area.
p. 169-196, 14 ill. n.b. et coul. (in Croatian, summary in Croatian and English).
Keywords: Bibliographie par pays, région ou ensemble géographique; Basilique (Rijeka, HRV); Camp militaire; Complexe ecclésial (Rijeka, HRV); Décor géométrique; Église (Rijeka, HRV) de l'Assomption de la Vierge; Narthex; Alpes juliennes; Kvarner; Rijeka